CONCEPTUAL FRAMEWORK OF THE EFFECT OF ISLAMIC FINANCIAL LITERACY ON PERSONAL FINANCIAL MANAGEMENT - Rustam Shaari; Siti Maziah Ab Rahman; Rikinorhakis Rizwan (Journal of Islamic, Social, Economics and Development, 2024)
This conceptual paper aims to explore the effect of Islamic financial literacy on personal financial management, focusing on the role of Islamic financial concepts, principles, and practices in enhancing financial decision-making and management among individuals. Drawing upon existing literature from Islamic finance, financial literacy, and personal financial management, we propose a framework that sheds light on the factors influencing the relationship between Islamic financial literacy and personal financial management. People's financial security is becoming a serious concern in light of the global economic climate. Acquiring expertise and comprehension of financial issues is the essence of financial literacy. This study's goal is to ascertain the financial literacy level of the B40 group, which consists of employees of the Tumpat Area Fishermen Association, as well as the impact of financial literacy on investment decisions, debt management strategies, savings plans, and retirement plans. Four independent variables make up the framework of this study: investment decision, debt planning, retirement plan, and savings plan. We then examine the concept of financial literacy, defining its key elements and highlighting its importance in enabling individuals to make informed financial decisions and manage their finances effectively. Subsequently, we explore the linkages between Islamic financial literacy and personal financial management, analyzing the ways in which Islamic financial concepts, principles, and practices can positively affect personal financial management practices.